2010
DOI: 10.1186/1741-7015-8-53
|View full text |Cite
|
Sign up to set email alerts
|

Routine resite of peripheral intravenous devices every 3 days did not reduce complications compared with clinically indicated resite: a randomised controlled trial

Abstract: BackgroundPeripheral intravenous device (IVD) complications were traditionally thought to be reduced by limiting dwell time. Current recommendations are to resite IVDs by 96 hours with the exception of children and patients with poor veins. Recent evidence suggests routine resite is unnecessary, at least if devices are inserted by a specialised IV team. The aim of this study was to compare the impact of peripheral IVD 'routine resite' with 'removal on clinical indication' on IVD complications in a general hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
108
3
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(134 citation statements)
references
References 33 publications
12
108
3
11
Order By: Relevance
“…En nuestro trabajo, la frecuencia de flebitis fue baja respecto a lo observado en otros estudios, lo que se explica por su diseño de tipo transversal y no de incidencia. No se incluyó en este estudio una evaluación sobre el reemplazo de CVP a plazos preestablecidos debido a que ha sido una política cuestionada por diferentes estudios observacionales, randomizados o revisiones sistemáticas que señalan que el riesgo de flebitis, obstrucción o bacteriemia por CVP no aumenta al prolongar el uso del CVP [4][5][6][7] . La decisión de no cambiar los CVP a plazos preestablecidos tiene múltiples beneficios que incluyen disminuir la carga laboral, evitar molestias al paciente y disminuir los costos por insumos [4][5][6][7]11 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…En nuestro trabajo, la frecuencia de flebitis fue baja respecto a lo observado en otros estudios, lo que se explica por su diseño de tipo transversal y no de incidencia. No se incluyó en este estudio una evaluación sobre el reemplazo de CVP a plazos preestablecidos debido a que ha sido una política cuestionada por diferentes estudios observacionales, randomizados o revisiones sistemáticas que señalan que el riesgo de flebitis, obstrucción o bacteriemia por CVP no aumenta al prolongar el uso del CVP [4][5][6][7] . La decisión de no cambiar los CVP a plazos preestablecidos tiene múltiples beneficios que incluyen disminuir la carga laboral, evitar molestias al paciente y disminuir los costos por insumos [4][5][6][7]11 .…”
Section: Discussionunclassified
“…Se consideró este criterio si había registro en relación a las condiciones del CVP dentro de las 12 hrs previas al estudio, donde al menos se debía mencionar la existencia del CVP. La permanencia del CVP fue evaluada pero no fue incluida como criterio de seguridad [4][5][6][7] .…”
Section: Artículo Originalunclassified
See 1 more Smart Citation
“…[28][29][30][31] Several recent studies have questioned current guidelines on the duration of PVC, reporting no conclusive benefit in routinely changing PVC after 72 hours. [32][33][34] However, present national guidelines recommend the removal or routine replacement of PVCs after 72 hours. 35 In particular, our current study has found an improvement in adherence to the above guidelines, with significantly fewer PVC in-situ for more than 72 hours post-intervention (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Small randomized clinical trials showed that IVC replacement based on clinical indication is safe in terms of development of phlebitis and other complications as compared to IVC routine replacement every 72-96 h [4,5]. Despite this evidence, the 2011 CDC guidelines designate clinically indicated replacement of IVC as an unresolved issue, indicating that more research is needed [2].…”
Section: Introductionmentioning
confidence: 99%